Improving the performance environment of a soccer team during a competitive season: An exploratory action research study - Pain, M. A.; Harwood, C.; Mullen, R. (The Sport Psychologist, 2012)
The aim of the current study was to facilitate systematic reflection and action to improve the performance environment of a soccer team during a competitive season. Using the Performance Environment Survey (PES; Pain & Harwood, 2007) as a diagnostic instrument, the researcher worked with the coach to collaboratively identify areas in which team preparation and functioning could be improved. Completed by the players and coach after each match, the PES captured feedback around team preparation and performance in the physical, psychological, coaching, social, planning/organizational and environmental domains. Analysis of this feedback provided the stimulus for weekly discussions with the coach. Results suggested that coach and player reflection increased during the study, and the coach reported that the PES data and his reflections on that data were beneficial to managing the performance environment. In areas where change was targeted—in particular the social and the physical domains—improvements in team functioning were reported. Team feedback meetings were also perceived as helpful to improving player ownership and cohesiveness.